Robot-Assisted Liver Resection and Cholecystectomy Using Indocyanine-Green for Intrahepatic Cholangiocarcinoma, in a Very Rare Anatomical Anomaly of 'Bipartite Liver'. (August 2022) - Ceccarelli, Graziano; Codacci-Pisanelli, Massimo; De Rosa, Michele; Mariani, Lorenzo; Rocca, Aldo; Mazzucca, Daniele; Polistena, Andrea
Robotic hepatobiliary surgery has significantly developed worldwide with substantial clinical results. Hepatobiliary anatomical anomalies increase the complexity of hepatobiliary resection with a relevant risk of iatrogenic lesions. Among congenital liver anomalies, the 'bipartite liver' is an extremely rare condition which might be associated with complex surgical dissection of the hepatic hilum. We herein report a rare case of congenital 'bipartite liver' associated with a cholangiocarcinoma of segment VI and calculous cholecystitis. The patient underwent robot-assisted segmentectomy and cholecystectomy with the use of indocyanine-green cholangiography and intraoperative ultrasound. A challenging hilar dissection was performed using this approach. To the best of our knowledge, this is the first case reported that describes a robot-assisted liver resection and cholecystectomy in a patient having a cholangiocarcinoma associated with this rare liver anomaly. The robotic approach was safe and effective and the 3D preoperative imaging, as well as the intraoperative green-indocyanine cholangiography was extremely useful, especially during hilar dissection and cholecystectomy.